Stress distribution of an upper central incisor restored with different posts - Hugo Sánchez-Bolívar; Edwin Chica-Arrieta; Federico Latorre-Correa (Universidad de Antioquia, 2009)
Introduction: the finite element method was used to analyze the stresses in teeth restored with posts. The variables studied were material and modulus of elasticity of dowel. Methods: the model of the post-restored tooth involved dentin, ligament, cortical and trabecular bone, gingiva, metal-ceramic crown, and gutta-percha. The dowels were made of zirconium, base metal and noble metal casting alloys. The dowel was cemented with resin luting agents. The variable included was modulus of elasticity and Poisson's ratio. A load of 200 N was applied to the crown an angle of 45 degrees in order to calculate the stress distribution and tensile shear also von misses stresses. Results: showed von Misses stress in dentin: Noble metal alloys 105.1899 N/mm2, base metal alloys 69.86746 N/(mm2) and zirconia 69.06321 N/mm2. Von Misses stress in dowel: Noble metal alloys 210.3797 N/mm2, base metal alloys 349.3373 N/mm2 and zirconia 345.3161 N/mm2. Conclusions: within the limitations of the study, it was found that increasing the elastic modulus of the post l was found to cause decreased dentin stress.